Transient 3D simulation of Czochralski crystal growth considering diameter variations - Raufeisen, Alexander; Breuer, Michael; Botsch, Tilmann; Delgado, Antonio (Journal of Crystal Growth, 2009)
For numerical simulations of the Czochralski crystal growth process, in the literature the quasi-steady state approach is used, i.e. the diameter of the crystal is kept constant. However, this leads to errors in the computation of the phase interface. In the present work, for the first time in 3D, the three-phase junction between melt, crystal and atmosphere is allowed to move in horizontal direction. Thus, diameter changes during the crystal growth process could be simulated accordingly. In the future, the vertical movement will be allowed as well, considering the free surface stresses. This will enable realistic predictions of the transient behavior of the crystallization front. © 2008 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2009.tech.ITC.stmmec.transi
Keywords: A1. Large-Eddy simulation; A2. Czochralski method; B2. Semiconducting silicon